9x-4x+2+1=-3x+7x-5

Simple and best practice solution for 9x-4x+2+1=-3x+7x-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-4x+2+1=-3x+7x-5 equation:


Simplifying
9x + -4x + 2 + 1 = -3x + 7x + -5

Reorder the terms:
2 + 1 + 9x + -4x = -3x + 7x + -5

Combine like terms: 2 + 1 = 3
3 + 9x + -4x = -3x + 7x + -5

Combine like terms: 9x + -4x = 5x
3 + 5x = -3x + 7x + -5

Reorder the terms:
3 + 5x = -5 + -3x + 7x

Combine like terms: -3x + 7x = 4x
3 + 5x = -5 + 4x

Solving
3 + 5x = -5 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
3 + 5x + -4x = -5 + 4x + -4x

Combine like terms: 5x + -4x = 1x
3 + 1x = -5 + 4x + -4x

Combine like terms: 4x + -4x = 0
3 + 1x = -5 + 0
3 + 1x = -5

Add '-3' to each side of the equation.
3 + -3 + 1x = -5 + -3

Combine like terms: 3 + -3 = 0
0 + 1x = -5 + -3
1x = -5 + -3

Combine like terms: -5 + -3 = -8
1x = -8

Divide each side by '1'.
x = -8

Simplifying
x = -8

See similar equations:

| ln(x-5)=ln(x+5)-ln(x-7) | | X=48-4p | | 5p+8+15p= | | 3y+3x=100 | | 4x-10=5x-x | | (-6x)-36=18-8x | | 0.50x+.20y=3.75 | | 14x-3=21 | | 2m+8+2(2m-3)=(m+3) | | 8x+11=118 | | -9x-21=-12-1 | | -40x+20=32x-26 | | 3x^3-11x^2+30=0 | | 0.5y=19.5 | | 15+3c+4d+2c= | | -5.895= | | 3(7-x)+6x= | | 27x+4=10 | | 0.375n=-0.75 | | P=3p-48 | | 9x+7(2x-4)=3-8x | | 3a-5=5a+3 | | 16x+24=15-20x | | (10x-3)+(6x+6)= | | 148x+2-4x-1=144x-252+20 | | 3(x+27)=-24x-6 | | 12--1/7a=-31 | | 2x+5x+10= | | X=x+1+x+2 | | 6x^2+66x-540=0 | | 4z-9= | | 2(2x-5)+10= |

Equations solver categories